2014
DOI: 10.3171/2014.6.spine13996
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic analysis of an artificial cervical disc: 7-year follow-up from the Prestige prospective randomized controlled clinical trial

Abstract: Object The authors assess the long-term safety and efficacy of cervical disc replacement with the Prestige Cervical Disc in a prospective, randomized, multicenter trial at 7 years of follow-up. Methods At 31 investigational sites, 541 patients with single-level cervical disc disease with radiculopathy were randomized to 1 of 2 treatment groups: 276 investigational group patients underwent anterior cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
198
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(215 citation statements)
references
References 26 publications
9
198
6
2
Order By: Relevance
“…Supplemental material is available with the online version of CORR 1 .). Finally, 12 eligible RCTs were included in our systematic review and meta-analysis [5,8,10,22,30,34,35,37,38,[42][43][44]. The study selection is shown in the PRISMA flowchart (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Supplemental material is available with the online version of CORR 1 .). Finally, 12 eligible RCTs were included in our systematic review and meta-analysis [5,8,10,22,30,34,35,37,38,[42][43][44]. The study selection is shown in the PRISMA flowchart (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…All 12 studies included in this meta-analysis were parallelgroup randomized trials, eight were conducted in the United States [5,8,10,22,30,35,38,44], and the other four were done in Asia and Europe [34,37,42,43] ( Table 1). The years of publication ranged from 2011 to 2015, and the lengths of followup ranged from 2 to 7 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these findings have not been consistent. Some studies show no difference between anterior cervical discectomy and fusion and cervical disc replacement, while others demonstrate superiority of cervical disc replacement [2,4,5].…”
mentioning
confidence: 99%